IMPROVING STUDENTS’ READING COMPREHENSION USING SCANNING TECHNIQUE - Edvieanto Edvieanto; Risman Munandar; Aris Munandar (PROJECT (Professional Journal of English Education), 2018)
The research was conducted in SMK LuhurBaladikain West Bandung. Reading has become the important instrument in education especially in teaching and learning. Reading comprehension is the activity of constructing the meaning of a reading that has important funding in the process of education and the success of students in learning. The research aims to find out the benefit of using scanning technique, and the specific target to be achieved in this research is to prove scanning technique to improve students’ reading comprehension. Output required of this research as a scientific publication in journal that have ISSN.  The design of this research is Classroom Action Research (CAR). From the result of pre-test, we found that students’ reading comprehension is under average, the score of pre-test is 59.00. After the implementation of scanning technique in every cycle, the students’ reading comprehension were getting better, it can be seen in average of post-test score cycle 1 was 68.5 and cycle 2 was 79.00. It can be concluded that scanning technique can improve students’ reading comprehension.